ZIP4 is required for normal progression of synapsis and for over 95% of crossovers in wheat meiosis - Draeger, Tracie N.; Rey, María-Dolores; Hayta, Sadiye; Smedley, Mark; Alabdullah, Abdul Kader; Moore, Graham; Martín, Azahara C. (Frontiers in Plant Science, 2023)
Tetraploid (AABB) and hexaploid (AABBDD) wheat have multiple sets of similar chromosomes, with successful meiosis and preservation of fertility relying on synapsis and crossover (CO) formation only taking place between homologous chromosomes. In hexaploid wheat, the major meiotic gene TaZIP4-B2 (Ph1) on chromosome 5B, promotes CO formation between homologous chromosomes, whilst suppressing COs between homeologous (related) chromosomes. In other species, ZIP4 mutations eliminate approximately 85% of COs, consistent with loss of the class I CO pathway. Tetraploid wheat has three ZIP4 copies: TtZIP4-A1 on chromosome 3A, TtZIP4-B1 on 3B and TtZIP4-B2 on 5B. Here, we have developed single, double and triple zip4 TILLING mutants and a CRISPR Ttzip4-B2 mutant, to determine the effect of ZIP4 genes on synapsis and CO formation in the tetraploid wheat cultivar ‘Kronos’. We show that disruption of two ZIP4 gene copies in Ttzip4-A1B1 double mutants, results in a 76-78% reduction in COs when compared to wild-type plants. Moreover, when all three copies are disrupted in Ttzip4-A1B1B2 triple mutants, COs are reduced by over 95%, suggesting that the TtZIP4-B2 copy may also affect class II COs. If this is the case, the class I and class II CO pathways may be interlinked in wheat. When ZIP4 duplicated and diverged from chromosome 3B on wheat polyploidization, the new 5B copy, TaZIP4-B2, could have acquired an additional function to stabilize both CO pathways. In tetraploid plants deficient in all three ZIP4 copies, synapsis is delayed and does not complete, consistent with our previous studies in hexaploid wheat, when a similar delay in synapsis was observed in a 59.3 Mb deletion mutant, ph1b, encompassing the TaZIP4-B2 gene on chromosome 5B. These findings confirm the requirement of ZIP4-B2 for efficient synapsis, and suggest that TtZIP4 genes have a stronger effect on synapsis than previously described in Arabidopsis and rice. Thus, ZIP4-B2 in wheat accounts for the two major phenotypes reported for Ph1, promotion of homologous synapsis and suppression of homeologous COs.